2016
DOI: 10.5897/ajar2016.10786
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and estimated losses caused by cassava viruses in Migori County, Kenya

Abstract: A farm survey was conducted in Kuria East and Suna West sub-counties to determine the incidence, severity and estimated losses of cassava brown streak disease (CBSD) and cassava mosaic disease (CMD) on cassava crops in farmers' fields. The results showed that cassava is the second most important staple crop after maize in Migori County. CMD incidence ranged from 0.0 to 56.7%) in Kuria East and 10.0 to 55.0% in Suna West. CBSD incidences were much higher at 5.0 to 74.0% in Kuria East and 10.0 to 77.5% in Suna W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
(23 reference statements)
3
13
0
Order By: Relevance
“…For example, in Uganda, where the latest CMD pandemic first emerged in the 1990s, the IITA varieties were resistant to CMD, and to a lesser extent, cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) in East Africa (Ntawuruhunga et al, 2013; Pariyo et al, 2015; Patil et al, 2015). Similar successes have been recorded in other eastern and southern African countries (Ntawuruhunga et al, 2013; Mbewe et al, 2015; Masinde et al, 2016). In Zambia, eight IITA varieties outperformed local varieties significantly, resulting in increased yields, household income, and food security (Khonje et al, 2015).…”
Section: Cmg Resistance Breedingsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, in Uganda, where the latest CMD pandemic first emerged in the 1990s, the IITA varieties were resistant to CMD, and to a lesser extent, cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) in East Africa (Ntawuruhunga et al, 2013; Pariyo et al, 2015; Patil et al, 2015). Similar successes have been recorded in other eastern and southern African countries (Ntawuruhunga et al, 2013; Mbewe et al, 2015; Masinde et al, 2016). In Zambia, eight IITA varieties outperformed local varieties significantly, resulting in increased yields, household income, and food security (Khonje et al, 2015).…”
Section: Cmg Resistance Breedingsupporting
confidence: 85%
“…Tuberous root losses due to CMD may reach 100% in highly susceptible varieties (Thresh et al, 1994; Masinde et al, 2016) or in mixed infections (Fondong et al, 2000a; Pita et al, 2001). Generally, there are three objectives to decreasing losses caused by virus diseases: (1) decrease the proportion of plants that become infected; (2) delay infection to such a late stage of crop growth that losses become unimportant; (3) decrease the severity of damage sustained after infection has occurred (Thresh and Cooter, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CBSD is caused by two distinct viruses: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) that generally cause similar root necrosis in infected plants (Bakelana et al, 2018;Legg et al, 2011;Masinde et al, 2016;Mbanzibwa et al, 2009;Ndunguru et al, 2015;Vanderschuren et al, 2012;Winter et al, 2010). CBSD-causing viruses are semi-persistently transmitted by the whitefly Bemisia tabaci (Gennadius) (Njoroge et al, 2017), however, aphids are been identified as potential vectors of CBSV (Ateka et al, 2017;Mulenga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report from Kenya estimates US$1,300/hectare losses [5]. Both viruses are transmitted by the whitefly vector Bemisia tabaci .…”
Section: Disease Impacts On Cassava In Africamentioning
confidence: 99%
“…The two viral diseases, CMD and CBSD, have a major impact on cassava production in sub-Saharan Africa, together causing estimated losses of US$1 billion per year [ 4 ]. A recent report from Kenya estimates US$1,300/hectare losses [ 5 ]. Both viruses are transmitted by the whitefly vector Bemisia tabaci .…”
Section: Disease Impacts On Cassava In Africamentioning
confidence: 99%